Effects of previous dynamic arm exercise on power output during repeated maximal sprint cycling - Bogdanis, G.C.; Nevill, M.E.; Lakomy, H.K.A. (Journal of Sports Sciences, 1994)
This study examined the effects of elevating blood lactate concentration by arm exercise on subsequent performance during repeated 30 s sprints with the legs. Eight male students performed two 30 s cycle ergometer sprints separated by 6 min of recovery, on two occasions. On one occasion the subjects performed only the two 30 s cycle ergometer sprints ('legs'), while on the other occasion 5 min of heavy arm cranking preceded the two sprints ('arms and legs'). Blood lactate concentration was determined from capillary samples at rest, after a standardized warm-up and 3 and 5 min following each exercise bout. In the 'legs' condition, the peak power output (PPO) and mean power output (MPO) in the second sprint were 92% (P < 0.05) and 85% (P < 0.01) of the values attained during the first sprint, respectively. Prior arm exercise, which increased blood lactate to 11.0 ± 0.6 mM, had no effect on PPO and MPO during the first cycle ergometer sprint (≃ 4% drop, N.S.). However, in the second sprint after prior arm exercise, PPO was 10% lower than the PPO attained during the corresponding sprint in the 'legs' condition (sprint 2 'arms and legs' 963 ± 42 W, sprint 2 'legs' 1074 ± 60 W, P < 0.05), while MPO was better maintained (sprint 2 'arms and legs' 517 ± 17 W, sprint 2 'legs' 549 ± 24 W, N.S.). The rate of blood lactate accumulation after both cycle ergometer sprints was considerably decreased (by ≃ 50%) when blood lactate levels were pre-elevated by arm crank exercise. It is suggested that the elevation of blood lactate levels by prior arm exercise can cause a significant drop in PPO of the second sprint by decreasing muscle buffering capacity and lactate/H+ efflux from the muscle. The less pronounced drop in MPO during the second sprint in the 'arms and legs' condition was assumed to be due to an increased aerobic contribution to energy supply.
Keywords: Blood lactate; Fatigue; Prior arm exercise; Recovery; Sprint cycling